The impact of information system-enabled supply chain process integration on business performance: a resource-based analysis - Ghobakhloo, Morteza; Tang, Sai Hong; Sabouri, Mohammad Sadegh; Zulkifli, Norzima (World Scientific Publishing, 2014)

(untitled)
This paper seeks to develop and test a model to examine the relationships between, technical aspects of IS resources (IS alignment, IS resources technical quality, IS advancement), supply chain process integration, and firm performance. A questionnaire-based survey was conducted to collect data from 227 supply chain, logistics, or procurement/purchasing managers of leading manufacturing and retail organizations. Drawing on resources-based view of the firm, and through extending the concept of process integration in supply network, as well as broadening the scope of role of IS resources in relation to process integration and performance gain from the focal firm to the entire supply chain, we found that supply chain process integration is an important multidimensional intermediate organizational capability through which the value of IS resources for supply chain management can be materialized. This capability serves as a catalyst in transforming the value of technical aspects of IS resources into higher performance gain for a firm. Thus, the importance of formation of all dimensions of this capability across supply network should be realized. Moreover, the result suggests that the technical aspects of IS resources need to be jointly developed by supply partners to effectively form supply chain capabilities.